2018
DOI: 10.1530/erc-17-0455
|View full text |Cite
|
Sign up to set email alerts
|

Telotristat ethyl in carcinoid syndrome: safety and efficacy in the TELECAST phase 3 trial

Abstract: Telotristat ethyl, a tryptophan hydroxylase inhibitor, was efficacious and well tolerated in the phase 3 TELESTAR study in patients with carcinoid syndrome (CS) experiencing ≥4 bowel movements per day (BMs/day) while on somatostatin analogs (SSAs). TELECAST, a phase 3 companion study, assessed the safety and efficacy of telotristat ethyl in patients with CS (diarrhea, flushing, abdominal pain, nausea or elevated urinary 5-hydroxyindoleacetic acid (u5-HIAA)) with <4 BMs/day on SSAs (or ≥1 symptom or ≥4 BMs/day … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
112
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 19 publications
(31 reference statements)
5
112
1
1
Order By: Relevance
“…All 12 studies reported efficacy and safety data from prospective, interventional, phase II or III clinical trials or pivotal clinical trials leading to drug approval; 3 were phase II [15-17], 6 were phase III [11-14, 18, 22], 1 was phase II/III [19], and 2 did not meet criteria for a phase II or III trial but were considered to be pivotal trials [20, 21]. The studies examined included 1,366 participants with NET, of which at least 1,137 had carcinoid syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All 12 studies reported efficacy and safety data from prospective, interventional, phase II or III clinical trials or pivotal clinical trials leading to drug approval; 3 were phase II [15-17], 6 were phase III [11-14, 18, 22], 1 was phase II/III [19], and 2 did not meet criteria for a phase II or III trial but were considered to be pivotal trials [20, 21]. The studies examined included 1,366 participants with NET, of which at least 1,137 had carcinoid syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…In the double-blind randomized phase III trial TELESTAR, telotristat ethyl significantly reduced bowel movement frequency with either the 250 or 500 mg TID dose versus placebo in patients with symptomatic carcinoid diarrhea while receiving stable-dose long-acting SSAs [12], and this antidiarrheal effect was confirmed by the double-blind randomized phase III TELECAST companion study of patients with carcinoid syndrome diarrhea (with or without SSA treatment) [11]. In TELESTAR and TELECAST, 40–44% of patients met predefined symptom response criteria in terms of bowel movement frequency reduction, compared with 0–20% of placebo-treated patients [11, 12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations